The Effect of Local Tax Policy Implementation on Increase in Regional Tax Revenues through Employee Performance Padang Lawas Regency - Revy Zunitha Nasution; Erlina; H.B Tarmizi (International Journal of Science, Technology & Management, 2021)
Tax is a citizen's obligation which is a form of service to the state whose reciprocity is not directly felt by taxpayers who are dynamic and follows the development of the country's social and economic life. The role of tax is very important as one of the backbones of state revenue, namely the source of government funds to carry out development both the central and local governments. Employee performance in carrying out their duties also plays an important role in efforts to implement local tax policies. The purpose of this study was to analyze the effect of implementing regional tax policies on increasing local tax revenue and to analyze the effect of implementing local tax policies through the performance of Padang Lawas Regency employees. The sample in this study was 50 employees of the Regional Revenue Agency of Padang Lawas Regency. The instrument used was a demographic data questionnaire, policy implementation, tax revenue, and employee performance. The method used in this research is a statistical quantitative approach research method with path analysis. The result showed that there was a significant influence between the implementation of regional tax policies on increasing local tax revenue through the performance of Padang Lawas Regency employees of Padang Lawas Regency.